Effect of fruit pulp and sugar concentration on the physicochemical, phytochemical and sensory characteristics of star fruit (Averrhoa carambola) leather - Gautam, Samiksha; Khadka, Nabin; Rai, Kishor (Vietnam Journal of Science and Technology, 2024)
Starfruit is an underutilized fruit and is rich in vitamin C. Fruit leather from starfruit was prepared in this study and analyses of its physicochemical, phytochemical, and sensory characteristics were performed. Five samples named A, B, C, D and E were prepared with different proportions of fruit pulp:sugar of 70:30, 75:25, 80:20, 85:15 and 90:10, respectively. All the prepared samples were subjected to analyses. Phytochemical contents were found to increase with increasing fruit pulp proportion, thus sample E (90:10) was found to be the best in terms of phytochemical content. Similarly, product sample C (80:20) was scored the highest by the panelist in terms of sensory aspect. The best product sample C had total soluble solids (TSS) of 31 ± 2 °Bx, total ash content of 2.482 ± 0.001 %, acid insoluble ash of 1.0013 ± 0.002 %, crude protein of 0.5902 ± 0.004 %, crude fat of 0.3514 ± 0.003 %, crude fiber of 0.8991 ± 0.003 %, carbohydrate of 95.67 ± 0.04 %, vitamin C of 24.24 ± 0.1 mg/100g, total energy of 338.11 ± 0.04 Kcal/100 g, total phenolic content (TPC) of 6.105 ± 0.001 mg GAE/g of dry extract, total flavonoid content (TFC) of 1.125 ± 0.002 mg QE/g of dry extract and DPPH scavenging activity of 27.268 ± 0.001 %. Panelists responded favorably to the prepared product samples.